Enhanced myocardial blood flow in ischemic cardiomyopathy by a slow-release synthetic prostacyclin agonist combined with coronary artery bypass grafting: The first human study in a Phase I/IIa clinical trial - Kawamura, Takuji; Yoshioka, Daisuke; Kawamura, Masashi; Matsuura, Ryohei; Kawamura, Ai; Misumi, Yusuke; Mikami, Tsubasa; Sawa, Yoshiki; Miyagawa, Shigeru (Frontiers in Cardiovascular Medicine, 2023)
Background: YS-1402, which is a polymerized form of the synthetic prostacyclin agonist ONO-1301, has been proven in several preclinical studies to induce therapeutic effects for patients with ischemic cardiomyopathy (ICM). In this human study, we assessed the safety, tolerability, and efficacy of YS-1402, combined with coronary artery bypass grafting (CABG), for ICM. Methods: Twenty-four patients with ICM whose left ventricular ejection fraction was <40% with an indication for CABG were double-blindly assigned to four groups: placebo, 10-mg YS-1402, 30-mg YS-1402, and 100-mg YS-1402. YS-1402 or placebo medications were administered on the surface of the left ventricle at the time of the CABG. Pre- and postoperative cardiac function and myocardial blood flow were assessed for 6 months postoperatively, along with a safety assessment. Results: No severe adverse events were related to YS-1402. The maximum blood concentration of ONO-1301 was less than that of the no observable adverse effect level. Significantly increased myocardial blood flow (MBF) and cardiac function were observed in the YS-1402 group 26 weeks postoperatively, although no improvement in MBF occurred in the placebo group. Conclusions: This Phase I/IIa parallel group-controlled, dose-escalation study of YS-1402 combined with CABG for ICM demonstrated the safety, tolerability, and potential efficacy of YS-1402.